2023
DOI: 10.1021/acs.jafc.3c01108
|View full text |Cite
|
Sign up to set email alerts
|

Antichilblain Components in Eggplant Based on Network Pharmacology and Biological Evaluation

Abstract: Eggplant, the fruit of Solanum melongena L. (Solanaceae), is applied externally to relieve the symptoms of chilblains in the folk in East Asia. However, the mechanisms and biological ingredients are not clear. A network pharmacology approach was used to shed light on the mechanisms of eggplant against chilblains, which illustrated that anti-inflammation and antioxidation are mainly involved in the curative effects. Bioassay-guided assays led to the isolation of 44 ingredients (1–44), including two new natural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 65 publications
(104 reference statements)
0
0
0
Order By: Relevance
“…Molecular docking studies with the five potential target proteins showed a high binding affinity, indicating their crucial roles in inhibiting the growth of hepatocellular carcinoma cell of compound 1 . It is worth mentioning that although the current study already showed great promise, the background information such as protein interaction networks, target information, and molecular pathways still remains to be updated, becoming more comprehensive and accurate. The network pharmacological approach to study the potential molecules not only explores the therapeutic potential of secondary metabolites but also aids in better understanding their potential adverse effects.…”
Section: Discussionmentioning
confidence: 94%
“…Molecular docking studies with the five potential target proteins showed a high binding affinity, indicating their crucial roles in inhibiting the growth of hepatocellular carcinoma cell of compound 1 . It is worth mentioning that although the current study already showed great promise, the background information such as protein interaction networks, target information, and molecular pathways still remains to be updated, becoming more comprehensive and accurate. The network pharmacological approach to study the potential molecules not only explores the therapeutic potential of secondary metabolites but also aids in better understanding their potential adverse effects.…”
Section: Discussionmentioning
confidence: 94%